The RhoA regulators Myo9b and GEF‐H1 are targets of cyclic nucleotide‐dependent kinases in platelets. (24th August 2020) - Comer, Shane; Nagy, Zoltan; Bolado, Alfonso; von Kriegsheim, Alexander; Gambaryan, Stepan; Walter, Ulrich; Pagel, Oliver; Zahedi, René P.; Jurk, Kerstin; Smolenski, Albert
Abstract: Background: Circulating platelets are maintained in an inactive state by the endothelial lining of the vasculature. Endothelium‐derived prostacyclin and nitric oxide stimulate cAMP‐ and cGMP‐dependent kinases, PKA and PKG, to inhibit platelets. PKA and PKG effects include the inhibition of the GTPase RhoA, which has been suggested to involve the direct phosphorylation of RhoA on serine 188. Objectives: We wanted to confirm RhoA S188 phosphorylation by cyclic nucleotide‐dependent kinases and to identify possible alternative mechanisms of RhoA regulation in platelets. Methods: Phosphoproteomics data of human platelets were used to identify candidate PKA and PKG substrates. Phosphorylation of individual proteins was studied by Western blotting and Phos‐tag gel electrophoresis in human platelets and transfected HEK293T cells. Pull‐down assays were performed to analyze protein interaction and function. Results: Our data indicate that RhoA is not phosphorylated by PKA in platelets. Instead, we provide evidence that cyclic nucleotide effects are mediated through the phosphorylation of the RhoA‐specific GTPase‐activating protein Myo9b and the guanine nucleotide exchange factor GEF‐H1. We identify Myo9b S1354 and guanine nucleotide exchange factor‐H1 (GEF‐H1) S886 as PKA and PKG phosphorylation sites. Myo9b S1354 phosphorylation enhances its GTPase activating protein function leading to reduced RhoA‐GTP levels. GEF‐H1 S886 phosphorylation stimulates binding of 14‐3‐3β and has been shown to inhibit GEF function by facilitating binding of GEF‐H1 to microtubules. Microtubule disruption increases RhoA‐GTP levels confirming the importance of GEF‐H1 in platelets. Conclusion: Phosphorylation of RhoA regulatory proteins Myo9b and GEF‐H1, but not RhoA itself, is involved in cyclic nucleotide‐mediated control of RhoA in human platelets.